Correlation of Malocclusion with Oral Health–Related Quality of Life and Socioeconomic Status among Libyan Schoolchildren - Mahadia Abdalrahman; Emni Elshaali; Fatheia Efhima (AlQalam Journal of Medical and Applied Sciences, 2026)
Malocclusion is a major contributor to oral health issues and has a significant negative effect on oral health-related quality of life (OHRQoL). A significantly underrepresented factor in research on OHRQoL is socioeconomic status (SES), particularly in developing and underdeveloped countries such as Libya. This study seeks to assess the relationship between malocclusion and OHRQoL in Libyan school children, as well as to examine the influences of socioeconomic factors. 350 Libyan school children aged 11-12 from both governmental and private schools participated in this study, which employed a cross-sectional design. The Dental Aesthetic Index (DAI) and the child perceptions questionnaire (CPQ 11-14) were used to assess malocclusion and OHRQoL, respectively. Parental education, income, and occupation are factors used in determining socioeconomic status (SES). Pearson’s correlation and Poisson regression were included in statistical analyses. A noteworthy relationship was found Pearson coefficients (r) and p-value between malocclusion features (DAI parts) and CPQ11-14 scores among 350 Libyan school-children. A significant negative correlation was observed between incisor diastema and the results demonstrated that CPQ11-14 scores increased with increasing severity of malocclusion. Children in grade 4 (DAI ≥36) exhibited the highest mean scores for all oral symptoms (17.2 ± 1.8) and total CPQ11-14 (119.4 ± 5.1), indicating a greater negative impact on oral health-related quality of life. In contrast, children in grade 1 (DAI ≤25) showed the lowest scores for oral symptoms (9.3 ± 1.9) and total CPQ11–14 (86.7 ± 5.9). The female participants faced more severe social and emotional impacts compared to their male counterparts (R 1.22, p < 0.01). This study concluded that malocclusion has a significant negative association with OHRQoL in children aged 11 to 12 years old, in additions socioeconomic status play an important effect on that relation. Females report considerably greater emotional and social effects.